THE IMPLEMENTATION OF PROBLEM BASED LEARNING (PBL) FOR IMPROVING CRITICAL THINKING AND STUDENT’S ACHIEVEMENT - Sri Rahayu; Johanes Sapri; Alexon Alexon (DIADIK, 2017)
The purpose of this study is to describe the application of Problem Based Learning (PBL) model to improve critical thinking and learning achievement of students and to know the effectiveness of the implementation of this model. The research methods were classroom action research and quasi experimental. The subjects of classroom action research were 10 students of Class V Public Elementary School 07 Talang Empat Bengkulu Tengah. The quasi-experimental population of the experiments is the 5th grader of SDN 05 Talang Empat and the samples are the V A class students as the experimental class and V B as the control class, each class consisted of 15 students. Data collection techniques for Classroom Action Research (CAR) were observation sheets to observe critical thinking activities and test instruments to measure achievement of learning objectives, and for quasi- experiments were test instruments. Data was analysed by measuring mean and t-test. The results of this study show: 1) there is an increase in critical thinking of students who learn with Problem Based Learning (PBL) model in every cycle; 2) there is an increase in student achievement with Problem Based Learning (PBL) model, and it make learning more effective. Keywords: Problem Based Learning, Critical Thinking Skill, and Student’s Achievement